Direct Fluoroalkylthiolation Based on Fluoroalkanesulfite Derivatives - Wei, Jingjing; Liang, Shuaishuai; Jiang, Lvqi; Yi, Wenbin (Synlett, 2023)
Fluoroalkylthio groups have received substantial attention in the past decade because of their unique physicochemical characteristics, and methods for incorporating these substituents into organic molecules have been rapidly developed in recent years. This account summarizes our efforts on the development of direct fluoroalkylthiolation with fluoroalkanesulfite derivatives. Several innovative and efficient strategies for the fluoroalkylthiolation of various substrates are disclosed, leading to various valuable fluoroalkylthiolated compounds in good yields.1 Introduction2 Fluoroalkylthiolation with Sodium Fluoroalkanesulfinate3 Fluoroalkylthiolation with Fluoroalkanesulfonyl Chloride4 Fluoroalkylthiolation with Other Fluoroalkanesulfite Derivatives5 Conclusion
Keywords: trifluoromethylthiolation; difluoromethylthiolation; organofluorine compounds; sodium trifluoromethylsulfinate; trifluoromethylsulfonyl chloride